2020
DOI: 10.3390/cells9081882
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1-PPARS Cross-Talk in Complex Metabolic Diseases and Inherited Disorders of the One Carbon Metabolism

Abstract: Sirtuin1 (Sirt1) has a NAD (+) binding domain and modulates the acetylation status of peroxisome proliferator-activated receptor-γ coactivator-1α (PGC1α) and Fork Head Box O1 transcription factor (Foxo1) according to the nutritional status. Sirt1 is decreased in obese patients and increased in weight loss. Its decreased expression explains part of the pathomechanisms of the metabolic syndrome, diabetes mellitus type 2 (DT2), cardiovascular diseases and nonalcoholic liver disease. Sirt1 plays an important role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 137 publications
(170 reference statements)
0
36
0
1
Order By: Relevance
“…Numerous findings provide evidence that natural ligands exhibit different binding affinities, which subsequently impact PPARα activation potency. Previous reports showed that omega-3 eicosapentaenoic acid (20:5, ω3) and, to a lesser extent, docosahexaenoic acid (22:6, ω3), are potent ligands [96,97] and consistent activators of PPARα [98][99][100], while omega-3 PUFA like linolenic acid (C18:3, ω3) and docosapentaenoic (22:5, ω3) acids, and omega-6 PUFA such as linoleic (C18:2, ω6) and arachidonic (C20:4, ω6) acids are weaker PPARα activators [74,99,100]. In addition, experiments performed by Ellinghaus et al and Zomer et al [101,102] revealed that phytanic acid (3,7,11,15-tertamethylhexadecanoic acid) is a strong natural physiological ligand for PPARα.…”
Section: Pparα Natural Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous findings provide evidence that natural ligands exhibit different binding affinities, which subsequently impact PPARα activation potency. Previous reports showed that omega-3 eicosapentaenoic acid (20:5, ω3) and, to a lesser extent, docosahexaenoic acid (22:6, ω3), are potent ligands [96,97] and consistent activators of PPARα [98][99][100], while omega-3 PUFA like linolenic acid (C18:3, ω3) and docosapentaenoic (22:5, ω3) acids, and omega-6 PUFA such as linoleic (C18:2, ω6) and arachidonic (C20:4, ω6) acids are weaker PPARα activators [74,99,100]. In addition, experiments performed by Ellinghaus et al and Zomer et al [101,102] revealed that phytanic acid (3,7,11,15-tertamethylhexadecanoic acid) is a strong natural physiological ligand for PPARα.…”
Section: Pparα Natural Ligandsmentioning
confidence: 99%
“…Essential coregulators are proteins deemed critical for the survival of the offspring, and their absence results in embryonic lethality: cAMP-response element-binding protein (CBP); PPAR-interacting protein/activating signal cointegrator 2 (PRIP/ASC2); PPAR-binding protein/mediator complex subunit 1 (PBP/Med1); mediator complex subunit 25 (Med25) [131][132][133]. Non-essential coregulators are proteins with such critical functional responsibilities that they are usually represented by more than one isoform-steroid receptor coactivators (SRCs) [131,132,134], Asp-Glu-Ala-Asp (DEAD)-box helicases [135][136][137], sirtuins (SIRT) [96,97], PPARγ coactivators (PGCs) [138][139][140][141]-and the loss of one isoform is compensated by others. Repressors that bind to the nuclear receptor PPARα in the absence of/or independent of ligands prevent it from binding to the peroxisomal proliferator response elements (PPRE) of the target genes as nuclear corepressor (NCoR) and silencing mediator of retinoic acid and thyroid hormone (SMRT) [96] (Figure 7A).…”
Section: Pparα and Coregulatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the use of liver-specific PPAR-null mice has opened the possibility of studying other important mechanisms in which PPARs are involved [ 149 ], mainly as mediators of epigenetic regulation mechanisms through their interaction with enzymes such as Sirtuin-1 [ 32 , 150 ], the regulation of PPAR promoters, through DNA methyltransferases (DNMTs) [ 151 ], and the regulation of their expression through a variety of microRNAs [ 152 ].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is widely involved in the metabolic control of intracellular substrates in the body. The decrease of SIRT1 expression and activity is a major characteristic of metabolic diseases, and its mechanism partly explains the influence of a high-fat diet on metabolic syndrome, obese diabetes, cardiovascular disease, and other related metabolic diseases (Kosgei et al, 2020 ). Decrease of SIRT1 expression can also lead to lipid accumulation and impaired insulin signaling in hepatocytes.…”
Section: Expression and Activity Of Sirt1 Decreased In Aging Neurodegenerative And Metabolic Diseasesmentioning
confidence: 99%